The Impact of Social Media on the Role of Social Media in the Kurdistan Region - قادر, م.م.سارة قادر; رەمەزان, ا.م.د. ئاراز رەمەزان احمد (Sulaimani Journal for Humanities, 2025)
This research has worked to present the extent of the impact of social networks on gender perspectives, in the Kurdistan Region, from the perspective of university teachers, to obtain information; The researcher used a special survey form with teachers of Kurdistan Regional Government (KRG) universities, including 500 teachers from public universities in the Kurdistan Region (KRG). Kurdistan and presenting the use of social networking platforms and (communication and influence) by building new trust, as well as knowing the level of use of social networking platforms and (communication and influence) by changing users' attitudes to gender perspective in the Kurdistan Region Socials by publishing articles. The researcher concluded that social networks are an effective engine for confronting attitudes on gender and involving social network users in discussions on gender issues so that they become the center for changing attitudes. Gender and gender perspectives by the sender also raise the level of information about gender issues. It has also been found that in the Kurdistan Region, social networks have a negative impact on consumer behavior related to gender perspectives and gender-related topics posted. Social networks have created a broad hub for communicating knowledge about gender perspectives to recipients, increasing the level of knowledge about gender perspectives and having a positive impact on the level of knowledge by increasing participation about gender perspectives